Salvage of Nipple-areolar Complex Venous Congestion Following Reduction Mammaplasty with Full-coverage Incisional Negative Pressure Wound Therapy - Celine Yi Ling Goh; Cindy Siaw Lin Goh (Journal of Plastic and Reconstructive Surgery)
Nipple-areolar complex necrosis following vascular compromise is an infrequent, but devastating complication of reduction mammaplasty. Negative pressure wound therapy has revolutionized wound care since its advent more than 20 years ago and has been used in various surgical settings. Here, we report the novel use of a full-coverage breast-specific incisional negative pressure wound therapy dressing in successfully salvaging nipple-areolar complex compromise in reduction mammaplasty.